Physiological and Metabolic Profiling of Women with Type 2 Diabetes and Former Gestational Diabetes - Chan, Sook Ni; O’Gorman, DJ; Yousif, O; Nolan, JJ (Trinity Student Medical Journal, 2002)
Objectives: Gestational diabetes mellitus (GDM) represents a variant of Type 2 diabetes with potential health consequences for both mother and baby. GDM is also a risk factor for the later development of Type 2 diabetes in women. The purpose of this study was to compare the physiologic and metabolic profile of women with Type 2 diabetes with a history of GDM to those without a history of GDM. Patients and Methods: A retrospective chart analysis was conducted on 176 female patients, including 28 (16%) with a prior history of GDM. A sub- group of 6 non-GDM and 3 GDM had an insulin modified (0.05 U/kg) intra-venous glucose (0.3 g/kg) tolerance test (IVGTT) to assess insulin sensitivity and first phase insulin secretion. Results: In our results, a history of GDM was associated with an earlier onset of diabetes (43.4±12.1 vs. 57.4±11.1 years for the GDM and non-GDM groups respectively, p<0.001). Despite having a longer duration of diabetes the lipid profile of the GDM group was similar, as was the HbA1c, body mass index, waist-to-hip ratio and blood pressure. The incidence of dyslipidemia (50% vs. 53% for the GDM and non-GDM groups respectively), hypertension (64.2% vs. 76.4%) and cardiovascular disease (14.3% vs. 29.2%) was similar between groups. Fasting plasma glucose was similar but fasting insulin was higher in the non-GDM group. Conclusion: Type 2 diabetes patients with a prior history of GDM have an earlier onset of diabetes. Screening for GDM should be universally performed to identify these patients early, and treatment should be instituted to delay or prevent the progression to Type 2 diabetes.